Authentically Growing an Influencer’s Following - Allen, Juliann; Wanjugu, Sabinah (Journal of Marketing Development and Competitiveness, 2024)
Marketers increasingly employ influencer marketing tactics to promote brands via social media, and consumer perceptions of influencers remain important—the way a consumer perceives an influencer can affect the way a consumer receives influencer messages. The study explores consumer perceptions of influencer authenticity based on how an influencer asks for a consumer to follow him or her. Using an experiment, the study examines the attitudes and intentions of consumers based on whether an influencer wants to increase follower count to either achieve a certain number of followers or to benefit followers with the content the influencer shares. The results reveal that an influencer who encourages a consumer to follow based on the benefits the consumer will receive is perceived as more authentic and is more likely to be followed by the consumer. On the other hand, an influencer who encourages a consumer to follow so that the influencer can achieve a higher number of followers is perceived as less authentic.